Impairment of gut defense barrier and microbial translocation in HIV-infection - G. R. Khasanova (Журнал инфектологии)
Translocation of bacterial components, including endotoxin of gram-negative microorganisms, is considered as one of the factors, contributing to hyperactivation of immune system in HIV-infection and progression of the disease. Possible reasons for increased intestinal permeability are discussed: massive loss of intestinal CD4-lymphocytes, especially during acute phase of disease, significant decrease in tight junction protein expression, on-going viral replication and constant inflammation of gut mucosa, altered gut micro ecology. Results of investigations of the role of microbial translocation in progression of HIV-infection are presented.